Factor Affecting Teacher Performance in Jabodetabek - Prasetyo, Johan Hendri; Ariawan, Joko (MANAZHIM, 2024)
This study seeks to comprehend and assess the factors that affect the performance of early childhood education (PAUD) teachers in the Greater Jakarta area (Jabodetabek). The research sample comprises 180 participants, who are PAUD teachers in Jabodetabek. A snowball sampling technique was utilized for participant selection. The data analysis was carried out using Structural Equation Model (SEM) with the SmartPLS (Partial Least Square) 3.2.8 software, encompassing both outer and inner model assessments to evaluate the research hypotheses. The study's outcomes reveal that self-efficacy, training, and achievement motivation have a substantial impact on the performance of PAUD teachers in Jabodetabek. Furthermore, self-efficacy and training affect the achievement motivation of PAUD teachers in Jabodetabek. Additionally, achievement motivation plays a mediating role in the relationship between self-efficacy, training, and the performance of PAUD teachers in Jabodetabek.